2015
DOI: 10.1038/cti.2015.18
|View full text |Cite
|
Sign up to set email alerts
|

Immunological evidence and regulatory potential for cell‐penetrating antibodies in intravenous immunoglobulin

Abstract: Anti-DNA cell-penetrating autoantibodies have been extensively studied in autoimmune but not in normal sera. We investigated herein the presence and properties of cell-penetrating antibodies (CPAbs) in intravenous immunoglobulin (IVIg), a blood product of pooled normal human IgG. IVIg cell penetration was observed into various cell lines, as well as cells from several organs of mice injected intravenously with IVIg therapeutic dose. In all cell types examined in vitro and in vivo, intracellular IgG localized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…24 Recently, it was also demonstrated that human IgG can directly permeate the cell membrane of various cell types, resulting in intracellular interactions that are incompletely understood. 25 This evidence expands the possible mechanisms of IgG-mediated regulation via its interactions with abT cells.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…24 Recently, it was also demonstrated that human IgG can directly permeate the cell membrane of various cell types, resulting in intracellular interactions that are incompletely understood. 25 This evidence expands the possible mechanisms of IgG-mediated regulation via its interactions with abT cells.…”
Section: Introductionmentioning
confidence: 52%
“…We used this cell culture model to elucidate the direct effect of interactions between soluble IgG and cell populations in the human thymus. In this context, 4 main interactions can occur: I-IgG antibodies can idiotypically interact with membrane clonal receptors expressed by immature lymphocytes, [26][27][28][29] with the Fab regions of IgG being responsible for mediating this effect; II-IgG can interact via FcgR receptors expressed on B cells and possibly on thymic dendritic cells (tDCs) and macrophages, [30][31][32] with the Fc regions of IgG playing a pivotal role; III-IgG can permeate the membrane and mediate cytoplasmic interactions, 25 with the diversity of the Fab regions of IgG being responsible for mediating these interactions; and IV-IgG can be processed and presented by antigen-presenting cells (including tDCs and B cells) in the context of MHC molecules for recognition by clonal receptors on immature T cells, 33,34 with both Fc-and Fab-derived peptides of IgG being involved.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it was considered that cell penetration by autoantibodies was likely to be a rare or aberrant phenomenon, which nevertheless could have important consequences for autoimmune disease, by influencing tolerance to intracellular selfantigen and by initiating apoptotic cell death [9,11,23]. Cell penetration has also been proposed as an intrinsic property of some germ-line encoded natural autoantibodies, which, if correct, has led to speculation of additional immunological functions for these molecules [2,24,25]. Importantly, it was also recognised that delivery of antibodies into the cell could open up new therapeutic areas [23].…”
Section: Identification Of Cell Penetrating Autoantibodiesmentioning
confidence: 99%
“…It was also recently shown that human IVIg can penetrate mouse, monkey and human cells, reacting with intracellular molecules such as DNA, histone and tubulin, and that human IVIg exhibits regulatory potential in murine splenocytes 53 . These effects are apparently more pronounced in CD4 T cells, with no influence observed in CD8 T cells.…”
Section: Introductionmentioning
confidence: 98%